PERKUATAN BALOK KONSOL TERHADAP GESER MENGGUNAKAN CARBON FIBER WRAP - IMMANUEL PANUSUNAN TUA PANGGABEAN; Valentana Ardian Tarigan (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2020)
Building structures, especially buildings, are always modified by the designer or building designer during the work. Changes that are made generally always result in an additional excess load from the initial plan on the structural members. The structural part reviewed in this study is a short console beam structure which is given a gradual increase in the load from the target load plan. Console beams are made using reinforced concrete material and formed by forming foundation plates and columns of reinforced concrete as a binding structure for these beams. The test is carried out after the specimen blocks have passed 28 (twenty eight) days of concrete and are given gradual loads until shear failure occurs. The console beam is then reinforced with carbon fiber wrap and is re-treated due to the use of epoxy or adhesive material for carbon fiber wrap adhesive with reinforced concrete. The test was carried out again by adding a gradual load to the failed structure reinforced with carbon fiber wrap. The test is carried out until the specimen fails or collapses. The results of this study conclude that the short console structure which is designed with a cross section size of 100 mm x 200 mm which experiences shear failure also experiences shear failure in its column. The increase in the strength of the short console beam after reinforced with Carbon Fiber Wrap is 83% for Test Object 1 with stirrup reinforcement f 6-150 and an increase of 85% for test object 2 with stirrup reinforcement f 6-100.